Numerical Simulation and Symmetry Reduction of a Two-Component Reaction-Diffusion System - Jina Li; Xuehui Ji (Advances in Mathematical Physics)
In this paper, the symmetry classification and symmetry reduction of a two-component reaction-diffusion system are investigated, the reaction-diffusion system can be reduced to system of ordinary differential equations, and the solutions and numerical simulation will be showed by examples.